Biodegradation of Mono-Hydroxylated PCBs by Burkholderia xenovorans LB400 - Tehrani, Rouzbeh (2012)
Three hydroxylated derivatives of PCBs, including 2′-hydroxy-4-chlorobiphenyl (2′-OH-4-CB), 3′-hydroxy-4-chlorobiphenyl (3′-OH-4-CB), and 4′-hydroxy-4-chlorobiphenyl (4′-OH-4-CB), were transformed by the PCB degrader, Burkholderia xenovorans LB400. When the bacterium was growing on biphenyl (biphenyl pathway-inducing conditions), all three hydroxylated isomers were significantly transformed. On the contrary, only 2′-OH-4-CB was transformed by the bacterium growing on succinate (conditions non-inductive of the biphenyl pathway). Gene expression analyses showed a strong induction of key genes of the biphenyl pathway (bph) when cells were grown on biphenyl, which is consistent with the transformation of the three isomers by biphenyl-grown cells. When cells were grown on succinate, only exposure to 2′-OH-4-CB resulted in expression of biphenyl pathway genes, which suggests that this isomer was capable of inducing the biphenyl pathway. These results provide the first evidence that bacteria are able to metabolize PCB derivatives hydroxylated on the non-chlorinated ring.